2016
DOI: 10.18632/oncotarget.9894
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of stem cell-related marker expression and its correlation with histologic subtypes in lung adenocarcinoma

Abstract: Cancer stem cells (CSCs) are a small subset of tumor cells that exhibit stem cell-like properties and contribute in treatment failure. To clarify the expression and prognostic significance of several CSC markers in non-small cell lung cancer, we retrospectively analyzed 368 patients with adenocarcinoma (n = 226) or squamous cell carcinoma (n = 142). We correlated the expression of six CSC markers – CD133, CD44, aldehyde dehydrogenase 1 (ALDH1), sex determining region Y-box 2 (SOX2), octamer binding transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 35 publications
3
43
0
Order By: Relevance
“…CD133, a glycoprotein known as Prominin 1 (PROM1), has been considered as a CSC marker in various solid tumors 43-46. It has been reported that CD133 expression correlates significantly with TNBC subtype 30, 47.…”
Section: Discussionmentioning
confidence: 99%
“…CD133, a glycoprotein known as Prominin 1 (PROM1), has been considered as a CSC marker in various solid tumors 43-46. It has been reported that CD133 expression correlates significantly with TNBC subtype 30, 47.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NANOG has been found frequently aberrantly expressed in a variety of human cancers, including head and neck squamous cell carcinomas (HNSCC) 6 , 7 . NANOG expression in cancer has been associated with chemoresistance 8 , 9 , epithelial to mesenchymal transition (EMT) 6 and poor clinical outcome 7 , 10 12 .…”
Section: Introductionmentioning
confidence: 99%
“…CD44 expression is reportedly correlated with long survival and predominantly lepidic subtypes in lung adenocarcinoma, consistent, in part, with our results. 28 In fact, one of the supportive explanations is that the interaction between CD44 and its ligand of hyaluronic acid may inhibit angiogenesis and progression of cancers. 29 The current World Health Organization classification scheme proposes that the new adenocarcinoma in situ and minimally invasive carcinoma categories represent a stepwise progression of Lepþ adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%